Indonesia-Oman Relationship: Gradually Growing with Many Opportunities - Muhamma Zulfikar Rakhmat (Kajian Asia Pasifik, 2021)
This paper aims to explore the relationship between the Republic of Indonesia and the Sultanate of Oman. Oman is one of the Middle Eastern countries which have strengthened its relationship with Indonesia. In recent years, Jakarta-Muscat ties have gradually developed in various spheres, although the cooperation remains limited compared to Indonesia’s ties with other regional states. Despite these developments, Indonesia’s ties with Middle Eastern countries has received little attention in the literature. This paper thus aims to examine the nature and scope of the relationship between Indonesia and Oman in a number of spheres based on Eberling (2017)’s five-dimensional framework, which includes political-diplomatic relations, economic-trade relations, military- security relations, cultural relations, as well as petroleum-energy relations. At the same time, the paper also intends to identify the opportunities available for the two countries to expand their ties.